Co‐expression of lipase isozymes for enhanced expression in Pichia pastoris. (3rd September 2017) - Cai, H.; Zhang, T.; Zhao, M.; Mao, J.; Cai, C.; Feng, F.
Abstract: To enhance the overall expression level of lipase isozymes which catalyse the same reaction in Pichia pastoris through co‐expression of isozymes from different sources; several types of co‐expression ways were constructed to determine the co‐expression efficiencies of lipase isozymes in P. pastoris . The results showed that the Kex2‐mediated co‐expression of lipase isozymes could express Rhizomucor miehei lipase (RML) and Thermomyces lanuginosus lipase (TLL) simultaneously, and GS‐ RMk‐kTL displayed an average lipase activity of 306·91 U ml −1, higher than GS‐ RML and GS‐ kTL (2·89 and 300·59 U ml −1 ) expressed independently in P. pastoris, and the sum of both (303·48 U ml −1 ), implying the potential of isozyme co‐expression mediated by Kex2 in increasing the overall recombinant expression, but the low recombinant expression of RML in P. pastoris weakened the overall increasing effect on lipase expression in the isozyme co‐expression strains. In addition, the fusion isozymes were successfully expressed, but with low lipase activities. Furthermore, 2A peptide could successfully mediate the co‐expression and secretion of lipase isozymes, but it seriously affected the expression of TLL downstream of 2A peptide. Significance and Impact of the Study: The low production level is one of the limitation factors for decreasing the prices of enzymes and expanding their application in industry as the biocatalysts. This research focuses on developing lipase isozyme co‐expression strategies in Pichia pastoris to enhance the expression level of overall lipase isozymes which catalyse the same reaction. The Kex2‐mediated co‐expression strategy of lipase isozymes could potentially enhance the overall isozyme expression, and isozyme co‐expression might provide a new direction for improving the recombinant isozyme expression, and decreasing the production and application prices of these mixed enzymes as biocatalysts Abstract : Significance and Impact of the Study : The low production level is one of the limitation factors for decreasing the prices of enzymes and expanding their application in industry as the biocatalysts. This research focuses on developing lipase isozyme co‐expression strategies in Pichia pastoris to enhance the expression level of overall lipase isozymes which catalyse the same reaction. The Kex2‐mediated co‐expression strategy of lipase isozymes could potentially enhance the overall isozyme expression, and isozyme co‐expression might provide a new direction for improving the recombinant isozyme expression, and decreasing the production and application prices of these mixed enzymes as biocatalysts.